2017
DOI: 10.1021/acs.jced.6b00909
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction of Rhenium(VII) from Aqueous Solution Assisted by Hydrophobic Ionic Liquid

Abstract: The solvent extraction of rhenium using TiOA as extractant assisted by ionic liquids from aqueous solutions was investigated. The molalities of ReO 4 − after extraction were measured at impurity ionic strength from 0.2 to 2.0 mol•kg −1 at temperatures from 293.15 to 318.15 K in the aqueous phase. Standard extraction constants K 0 at different temperatures were obtained by the Pitzer polynomial approximation method. Thermodynamic properties for the extraction procedure were also calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
(21 reference statements)
0
14
0
Order By: Relevance
“… 6 However, reserves of Re in the nature were seriously insufficient, and the quality of minerals was low, added to the extreme imbalance of minerals in distribution, the shortage of Re existed extensively naturally, which had impeded the development of superalloy industries and downstream industries seriously. 7 On the other hand, the metallurgical process of Re was not reasonable enough because the separation and purification was much inefficient. The separation and purification process was undertaken by the ion exchange method mainly for the moment, but the selectivity of this method was very poor.…”
Section: Introductionmentioning
confidence: 99%
“… 6 However, reserves of Re in the nature were seriously insufficient, and the quality of minerals was low, added to the extreme imbalance of minerals in distribution, the shortage of Re existed extensively naturally, which had impeded the development of superalloy industries and downstream industries seriously. 7 On the other hand, the metallurgical process of Re was not reasonable enough because the separation and purification was much inefficient. The separation and purification process was undertaken by the ion exchange method mainly for the moment, but the selectivity of this method was very poor.…”
Section: Introductionmentioning
confidence: 99%
“…However, in that study, a phase modifier was also required. More recent studies using ILs as diluents used around 1% (w/w) of amine extractant (triisooctylamine) to obtain over 99% extraction of this metal ion from acid solutions 4,20 . In this work, only 3% (v/v) of [TOMA][BA] allows the extraction of around 95% of Re(VII) using an organic‐solvent‐free extracting solution without any phase modifier.…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies using ILs as diluents used around 1% (w/w) of amine extractant (triisooctylamine) to obtain over 99% extraction of this metal ion from acid solutions. 4,20 In this work, only 3% (v/v) of [TOMA][BA] allows the extraction of around 95% of Re(VII) using an organic-solvent-free extracting solution without any phase modifier. On the other hand, it has been also demonstrated that the use of ILs as diluents enhances the extraction percentages.…”
Section: Process Parameters Effect Of the Initial Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Many methods, such as capillary electrophoresis, chemical deposition, liquid chromatography, ion exchange, and solvent extraction, are used to separate and enrich rhenium. Solvent extraction provides an effective and simple separation method; it is often used for the recovery of rhenium from molybdenum. …”
Section: Introductionmentioning
confidence: 99%